Synthesis and characterization of bio-composite nanofiber for controlled drug release - Pal D.B.; Srivastava P.; Mishra A.; Giri D.D.; Srivastava K.R.; Singh P.; Awasthi S.; Kumari L.; Mishra P.K. (My University, 2025)
In the present study, nanofiber mats of polyvinyl alcohol (PVA), polyvinyl acetate (PVAc) and 1:1 (w/w) PVA & PVAc (multi-component composite) have been developed and evaluated for the sustained release of broad spectrum antibacterial drug ‘ciprofloxacin HCl’. These nanofiber mats were developed through electrospinning the solutions of these non-toxic and biocompatible polymers (i.e. Drug PVA and PVAc) individually, as well as in 1:1 (w/w) mixed condition (i.e. composite). Prior to the electrospinning (about 1.5 h), 5%, 10% and 15% w/w ciprofloxacin HCl (CipHCl) was also homogeneously mixed in these polymer solutions. Results indicate that the average diameter of PVA, PVAc and multiple-component composite (PVA/PVAc) fibers without drug loading was 59.5, 93.3 and 183.7 nm, respectively. Moreover, the average diameter for drug multiple-component composite (1:1) fibers with increasing drug concentration (i.e. 5%, 10% and 15%) was 171, 163.5 and 162.4 nm, respectively. XRD analysis of these nanofiber mats showed higher surface property, which is indicated by only weak signals for the characteristic peaks with increasing drug concentration. For 5% CipHCl loading, the drug released from drug-multiple-component composite was intermediate (∼29%) as compared to PVA (∼50%) and PVAc (∼13%). However, the drug multiple-component composite mats exhibited the property of extended drug release for 10 days as compared to complete drug release of 6 days in case of both drug PVA and PVAc nanofiber mats. It indicates that the addition of PVAc promotes the sustained release of drug via its enhanced water stability, and reduced fiber swelling and initial burst of drug release. © 2017